Eufrosina regressa à escola - Pereira, Silvina (2012)
The article refers to theatrical representations in universities and colleges, including the University of Coimbra, mentioning specifically the triangle consisting of Sá de Miranda, Jorge Ferreira de Vasconcelos and Antonio Ferreira. From the Comedy Euphrosyne of Jorge Ferreira de Vasconcelos, it also intended to make a reflection about the presence of the classics today, allowing the resumption of a theatrical tradition, in school and at University. The experience of staging of a juvenile version of Euphrosyne showed that this is a dramaturgy exemplarily alive and that has much to say to our contemporaneity.